2005
DOI: 10.1111/j.1365-2052.2005.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mapping of the fragile histidine triad (FHIT) gene in cattle, river buffalo, sheep and goat by FISH and assignment to BTA22 by RH‐mapping: a comparison with HSA3

Abstract: Common fragile sites can be damaged by exposure to a variety of carcinogens. The fragile histidine triad (FHIT) gene, including the most active human chromosomal fragile site (FRA3B) at chromosome band HSA3p14.2,1 has been proposed as a tumour suppressor gene for a variety of tumours.2 The most common response to carcinogen exposure is deletions at the FHIT locus that alter the gene structure and function. In this study we assign the FHIT gene in cattle, river buffalo, sheep and goat chromosomes by comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Second, BACs bI0643H09 and bI0947B04, boxed in Figure [see Additional file 2 ], could be directly linked in the contig, as they were both positive to the intron 8–1 tag. Third, the sequence of the BAC-ends, available for clones bI0195D05, bI0520A05, and bI0545B04, was BLASTed to the bovine genome database and identified a contig assigned to BTA11 [Genbank: NW_988236 ], which is extraneous to the FHIT bovine locus, previously mapped to BTA22 [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, BACs bI0643H09 and bI0947B04, boxed in Figure [see Additional file 2 ], could be directly linked in the contig, as they were both positive to the intron 8–1 tag. Third, the sequence of the BAC-ends, available for clones bI0195D05, bI0520A05, and bI0545B04, was BLASTed to the bovine genome database and identified a contig assigned to BTA11 [Genbank: NW_988236 ], which is extraneous to the FHIT bovine locus, previously mapped to BTA22 [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous report, we mapped the FHIT gene by FISH and radiation hybrids using a bovine EST that matched human exon 9 [ 10 ]. Here we designed primers on the human FHIT cDNA to cross-amplify the bovine cDNA by means of RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two available buffalo genome sequences on the NCBI platform are not displayed on chromosomes and genes are not annotated (UMD CASPUR WB 2.0; https://www.ncbi.nlm.nih.gov/assembly/GCF_000471725.1/ ). Cattle and buffalo have been reported to be closely related, sharing homology in chromosome banding and gene mapping [ 49 , 50 ]. It has also been confirmed that the bovine genome is a useful source of markers for buffalo genome mapping [ 51 , 52 ], three available buffalo GWAS were constructed using the cattle genome reference [ 4 , 18 , 53 ].…”
Section: Methodsmentioning
confidence: 99%